PENGARUH KARAKTERISTIK SOSIODEMOGRAFI TERHADAP SELF EFFICACY PEREMPUAN KELUARGA MISKIN DALAM MELAKSANAKAN USAHA EKONOMI PRODUKTIF DI SURAKARTA - Suminah Suminah; Sunarru Samsi Hariadi; Sri Widodo; Sri Peni Wastutiningsih (SEPA: Jurnal Sosial Ekonomi Pertanian dan Agribisnis, 2014)
This  study  aimed  to  analyze  the  influence  of  sociodemographic characteristics  to  the  self-efficacy  on  women  of  poor  households  (WPH)  in implementing  economically  productive  activities.  The  study  was  conducted  at Surakarta,  using  a  survey  approach.  Samples  were  taken  by  multistage  random sampling technique. Quantitative data were analyzed using multiple regression models. The  results  showed  that  the  factors  sociodemographic  characteristics:  age,  formal education, and the number of family dependents significant affect on self-efficacy of WPH  in  conducting  productive  business  at  significance  level  α  =  0.10,  whereas  the non-formal  education  and  long  effort  had  no  significant  affect.  Goodness  of  fit  test results  of  multiple  linear  regression  model  showed  that  the  sociodemographic characteristics collectively have the affect of 28.6 percent.